Financial Constraint Effects on R&D: Evidence from US Firms - Zhao, Peng (2016)
Recently, R&D has become increasingly significant inputs for innovations. Compared with capital investments, R&D investment is more susceptible to financial constraints because R&D investments suffer more asymmetric information and lack collateral value. However, a large number of related studies focus on R&D to cash holdings sensitivities, but the effect of financial constraints and some essential characteristics, such as R&D smooth. The main subject of this study is to research how financial constraints affect the R&D financing by investigating 5512 U.S. public traded firms during the period of 2005 to 2015. This study applies dynamic investment model and uses system GMM method to estimate the relationships between financial constraint, related financial variables and R&D investment. Our findings indicate that financially constrained firms actively manage liquidity in order to sustain R&D investment; additionally, issuing stock is another important external funds source for R&D financing for financially constrained firms.